Exploring the Impact of Marvelous Dynamics on Fans’ Perception, Behavior, and Pop Culture - Purwaningsih, Rita; Gustini, Leili Kurnia; Sumarni, Teti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study investigates the relationship between Marvel and its fanbase, with a particular emphasis on the X online community (@Marvfess). Employing a phenomenological qualitative approach, data was collected through interviews and observations involving individuals aged 18-25 who actively engage with @Marvfess on X. Furthermore, data triangulation was conducted by consulting a social media and branding specialist as well as a psychologist. The research aims to evaluate the impact of Marvel’s interactions with its fans on brand perceptions, the influence of these interactions on fan behavior, and their contribution to broader trends in popular culture. Drawing on Goffman’s Theory of Self-Expression, Social Presence Theory, and Jenkins’ Participatory Culture, the findings indicate that Marvel’s engagement with its online community fosters a strong connection, significantly shaping fans’ perceptions and behaviors, and driving trends in popular culture through active fan participation